Peningkatan Literasi Mahasiswa tentang Ultra Processed Food dan Sedentary Lifestyle melalui Forum Diskusi Ilmiah - Kinasih, Prananingrum; Miftahul Jannah; Adelia Paradya Zetta; Beatrice Cynthia Walter (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Changes in modern lifestyles have driven the emergence of a dual epidemic characterized by increased consumption of ultra-processed foods (UPF) and a sedentary lifestyle. As a productive age group, college students are at high risk for both of these factors due to unhealthy activity patterns and consumption habits. This scientific discussion forum aims to improve students’ literacy regarding UPF and sedentary lifestyles. The method used was an interactive discussion involving faculty members as resource persons and students as participants. The activity was held on November 14, 2025, in the video conference (ViCon) room at Batam International University with 24 participants. The results of the activity showed an increase in students’ knowledge and awareness regarding the characteristics of UPF, its impact on health, and the risks of a sedentary lifestyle. Students also demonstrated a critical attitude in choosing consumption patterns and began to realize the importance of physical activity. The conclusion of this activity is that scientific discussion forums are effective as an educational medium in improving student literacy regarding the double epidemic and strengthening the role of students as agents of change in implementing and disseminating healthy lifestyle behaviors. Keywords: health education; sedentary lifestyle; student literacy; ultra processed food.   Abstrak Perubahan gaya hidup modern telah mendorong terjadinya fenomena epidemi ganda yang ditandai dengan meningkatnya konsumsi UPF dan sedentary lifestyle. Mahasiswa sebagai kelompok usia produktif memiliki risiko tinggi terhadap kedua faktor tersebut akibat pola aktivitas dan kebiasaan konsumsi yang kurang sehat. Kegiatan forum diskusi ilmiah ini bertujuan untuk meningkatkan literasi mahasiswa terkait UPF dan sedentary lifestyle. Metode yang digunakan adalah diskusi interaktif yang melibatkan dosen sebagai narasumber dan mahasiswa sebagai peserta. Kegiatan dilaksanakan pada 14 November 2025 di ruang video conference (ViCon) Universitas Internasional Batam dengan jumlah peserta sebanyak 24 orang. Hasil kegiatan menunjukkan adanya peningkatan pengetahuan dan kesadaran mahasiswa terkait karakteristik UPF, dampaknya terhadap kesehatan, serta risiko sedentary lifestyle. Mahasiswa juga menunjukkan sikap yang kritis dalam memilih pola konsumsi dan mulai menyadari pentingnya aktivitas fisik. Kesimpulan dari kegiatan ini adalah forum diskusi ilmiah efektif sebagai media edukasi dalam meningkatkan literasi mahasiswa mengenai epidemi ganda serta memperkuat peran mahasiswa sebagai agen perubahan dalam menerapkan dan menyebarluaskan perilaku hidup sehat. Kata kunci: edukasi kesehatan; literasi mahasiswa; sedentary lifestyle; ultra processed food.